Taxis and crowd-taxis: sharing as a private activity and public concern - Merethe Dotterud Leiren; Jørgen Aarhaug (Internet Policy Review, 2016)
The sharing economy has generated interest among economists for its customer focus and potential to enhance competition. However, it has also caused uproar in industries which have felt competitive pressure, for example among the established stakeholders in the taxi industry. While regulations currently impose considerable costs on the taxi industry, they do not cover virtual transport innovations such as Uber. The lack of a level playing field between taxis and such 'crowd-taxis' has generated media attention and conflict. Taxi owners worry about decreasing revenues and taxi drivers about poor working conditions. Other concerns are related to poor transport preparedness, accessibility issues, quality assurance and tax evasion. Despite considerable media attention, there has so far been a lack of scholarly literature addressing the consequences of the sharing economy in the transport sector. Focusing on the Norwegian taxi market, we argue that crowd-taxis will likely produce a range of unanticipated effects, necessitating regulation. For example, crowd-taxis may contribute to a loss of transport preparedness in rural areas. The findings are based on first and secondary data and 19 interviews.
Keywords: 300; Sharing economy; Transport; Crowdworking